An example of problems associated with DNA barcoding in tardigrades: a novel method for obtaining voucher specimens - Cesari, Michele; Giovannini, Ilaria; Bertolani, Roberto; Rebecchi, Lorena (Zootaxa, 2011)
We have in recent papers revealed that an integrative taxonomy approach helps to solve taxonomic problems in tardigrades. However, whole tardigrades are required for DNA work, which leaves no hologenophore voucher specimens with adult morphology. Using a novel methodology for the Tardigrada, we introduce the practice of collecting high quality maximum magnification light microscopy images of recently thawed animals to act as hologenophore voucher specimens of animals later used for DNA barcode sequencing. Within the framework of a DNA barcoding project on tardigrades, we collected a moss sample from the type locality of Macrobiotus terminalis Bertolani & Rebecchi, 1993 (Castelsantangelo, Central Apennines, Italy), a species of the “Macrobiotus hufelandi group”. Within the moss sample we found several animals and eggs with a morphology that corresponded to the original description of M. terminalis, while others were attributable to Macrobiotus macrocalix Bertolani & Rebecchi, 1993. In this study, molecular (cox1 mtDNA) analyses demonstrated no intraspecific variability in M. terminalis from the type locality but very large interspecific differences when compared with M. macrocalix and GenBank data for other species within the M. “hufelandi group”. There was also a large difference between our M. terminalis sequences and the GenBank data of a specimen attributed to the same species. The GenBank sequence originated from a population in the Northern Apennines, whose morphology appeared to be like that of the specimens of the locus typicus. This confirmed the importance in utilising material from the type locality for linking molecular data to the species’ morphological characters. Our paper underlines the importance of an integrative taxonomy in species diagnoses and demonstrates a scenario where morphological observations alone are not always sufficient. Lastly, this work adds reliable information to the sequence reference library that provides a useful building block for further studies on similar and related tardigrade taxa.